Building Professional Relationships and Student Confidence through Early Childhood Graduate Practitioner Competencies - Tanya Richardson; Su Lavercombe; Sigrid Brogaard-Clausen (Journal of Teaching and Learning for Graduate Employability)
This paper reports on how Early Childhood Graduate Practitioner Competencies (ECGPCs) impact on professional relationships and develop bidirectional confidence in the practical abilities of Early Childhood Studies (ECS) students in England. The study adopted an interpretive approach, seeking views through questionnaires (n=38) which were administered, through purposeful sampling, to students, mentors and academics from three universities in England offering Early Childhood Studies (ECS) degrees with ECGPCs. Findings suggest that the ECGPCs enabled focused placement students, with stakeholders recognising the potential for confidence and increased professionalism through the direction that the ECGPCs provide. In contexts of rapid change in Early Childhood policy this article argues the importance of the ECGPCs and of placement to support the graduate professional identity of the early childhood workforce. Interlinking and evidencing knowledge from research and practice enable graduates to articulate and have competencies in; ‘what they do’, ‘how they do ‘it’’ and essentially ‘why they do ‘it’’’. This is essential in promoting graduate relational/collegial professionals and advocating for stronger societal recognition and valuing of young children and the professionals working with them. With the ECGPCs being a new initiative within the United Kingdom, this study is unique in that it begins the research conversation around the success and challenges that this new initiative brings to the suite of Early Childhood (EC) qualifications.